2017
DOI: 10.18203/2320-1770.ijrcog20175265
|View full text |Cite
|
Sign up to set email alerts
|

IUFD incidence, causes and complications: a retrospective study done at a tertiary care centre in greater Noida, India

Abstract: Background: Demise of a fetus is not only a cause of distress to the parents but also leaves the obstetrician with little choice. Managing such a pregnancy and counselling of the patient becomes a difficult task for us. Early assessment and timely intervention are the key approaches for reducing the incidence of still births globally. By such a strategy, peripartum complications can also be reduced. The current study was undertaken with an aim to assess the incidence of IUFD, causes and peripartum complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
12
4
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 5 publications
(7 reference statements)
9
12
4
2
Order By: Relevance
“…IUFD due to Hypertension in pregnancy is due to placental insufficiency which can be prevented or reduced by qualitypreconceptional and antenatal care. In present study Abruptio placenta is the second common cause 15%, another study had showed it 19.87% which is comparable to present study but Jamal S found it as high as 30.03% this condition can be reduced by antenatal care by controll of Blood Pressure and supplementation of Folic acid 5,6 . Present study showed Diabetes Mellitus (DM) as a cause in 13% cases , but Pattanaik showed it 5.5% which is much lower than our observation 7 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…IUFD due to Hypertension in pregnancy is due to placental insufficiency which can be prevented or reduced by qualitypreconceptional and antenatal care. In present study Abruptio placenta is the second common cause 15%, another study had showed it 19.87% which is comparable to present study but Jamal S found it as high as 30.03% this condition can be reduced by antenatal care by controll of Blood Pressure and supplementation of Folic acid 5,6 . Present study showed Diabetes Mellitus (DM) as a cause in 13% cases , but Pattanaik showed it 5.5% which is much lower than our observation 7 .…”
Section: Discussionsupporting
confidence: 86%
“…Although the overall perinatal mortality has decreased in past three decades, the number of IUFD is higher as compared to that of early neonatal deaths. Usually intrauterine fetal death is diagnosed in the antenatal period by history (i.e less fetal 81% which is much lower than our study 5,6 . IUFD due to Hypertension in pregnancy is due to placental insufficiency which can be prevented or reduced by qualitypreconceptional and antenatal care.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The rate of IUFD and still birth directly point towards the quality of Antenatal Care received by the patient in the society. 2 In most of the cases, IUFD is unexpected and hence difficult to explain the exact cause of it in many cases.…”
Section: Introductionmentioning
confidence: 99%
“…3 Worldwide over 2.6 million stillbirths happen annually of which 23.2% were from India. 2 A vast majority (98%) of IUFD occur in developing countries. 1 It is important to diagnose the cause of IUFD in order to avoid further recurrence and to treat any maternal associated factors.…”
Section: Introductionmentioning
confidence: 99%